PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, KEBIJAKAN DIVIDEN, DAN GOOD CORPORATE GOVERNANCE (GCG) TERHADAP NILAI PERUSAHAAN - B31112126, Maria Ulva (Jurnal Manajemen Update, 2016)
The study aims to know the influance of the investment decisions, funding decisions, dividend policy and good corporate governance (GCG) that proxied using managerial ownership, audit committe, and independent commissioner. The study population is companies that incorporated in LQ45 indexs in Indonesia stock exchange (ISE) on 2010-2014 this study of 20 companies that incorporated in LQ45 indexs with observation data as much as 100 data. Sampel selection usus purposive sampling method. The study analysis method uses multiple linear regression SPSS 16.0 program. The results of this study indicate that (1) investment decisions give negative influences significantly to the value of company (2) funding decisions give positive influences significantly to the value of company (3) dividend policy gives positive influences significantly to the value of company (4) good corporate governance (GCG) that proxied using managerial ownership gives negative influences insignificantly, audit committe gives negative influences insignificantly and independent commissioner gives positive influences significantly to the value of company. Keywords: investment decisions, funding decisions, dividend policy and good corporate governance (GCG) that proxied using managerial ownership, audit commite, and independent commissioner